Upravljanje s prostorskimi podatki na terenskem računalniku - Šumrada, Radoš (Geodetski vestnik, 2000)
Paper describes the application of field (mobile pen) computers for spatial (geographical) data gathering and maintenance. The emphasis is on topographic data (digital large-scale maps) and cadastral data (digital cadastral maps) updating. Recent attempts in Slovenia are oriented to further automation of data field collection methods that are based on electronic tachometers (total station) and GPS rovers. The research was oriented towards the real time acquisition of various attributes (location, description and time) for topographic and cadastral spatial objects
Keywords: geodesy; geodezija; GIS; management; prostorski podatki; upravljanje